Synthesis of metal semiconductor hybrid nanostructures for light-driven chemical reactions - Neo, Peng Hui (Nanyang Technological University, 2022)
Polymeric carbon nitride – Titanium dioxide – Platinum (PCN-TiO2-Pt), was synthesized through a series of processes including solvothermal, hydrolysis, annealing and photo-deposition to investigate its photocatalytic efficiency. PCN-TiO2-Pt material consists of hybrid heterojunctions: metal-semiconductor (M-S) and semiconductor-semiconductor (S-S) junctions.